Debris Analysis in RDNK Site Serpong due to Bridge Blockage Simulations Using HEC-RAS - Yuliastuti Yuliastuti (Lowland Technology International, 2020)
The objective of this paper is to investigate the debris analysis due to bridge blockage by observing the rising of surface water elevation on the designated bridge based on the HEC-RAS simulation module. Methodology used in this paper covers the preparation of RAS geometry, determination of hydrological parameters, and RAS mapping for the output. Bridge and debris modelling were performed using the floating-pier debris module. Simulation was performed under the unsteady flow simulations. Simulation result showed that there were 3 m of water level increase during the blockage scenario. Keywords: Floating debris, Bridge, HEC-RAS, Pier